Introduction to NASA Living With a Star Institute Special Section on Low Earth Orbit Satellite Drag: Science and Operational Impact. Issue 8 (25th August 2018) - Zhang, Yongliang; Paxton, Larry J.; Jones, James C.
Abstract: This paper provides a brief description of the NASA Living With a Star (LWS) Institute special section on low Earth orbit (LEO) satellite drag: Science and operational impact. The goals of the LWS institute are to (a) review the current status of atmospheric drag research and operational concerns for LEO satellites, (b) identify and understand the major issues in atmospheric drag estimation, and (c) provide recommendations for future improvement in our ability to provide nowcasts of satellite drag. This special section presents the progress made by the 17 institute members of the 11 participating institutes from four countries as well as additional contributions from scientists who were not part of the original NASA LWS LEO drag team. Contributions cover topics in measurement and modeling of solar extreme ultraviolet inputs, thermospheric neutral density profiles, changes in composition and total density, and satellite conjunction and orbit prediction. Errors in the thermosphere density specification are the dominant source in uncertainty of LEO drag estimation and satellite conjunction. The consensus opinion is that significant funded future effort needs to address and improve measurements and modeling of the thermospheric neutral density and composition under different solar and geomagnetic conditions. Key Points: A brief introduction to 16 papers in the special section Variations in LEO satellite drag is dominated by changes in the thermospheric neutral density and composition A better solar EUV proxy is needed for thermospheric modeling. Satellite conjunction is greatly impacted errors in themospheric density